2021
DOI: 10.1080/2162402x.2021.2015113
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses to adjuvant vaccination with combined CD1c+ myeloid and plasmacytoid dendritic cells in stage III melanoma patients

Abstract: We evaluated the immunological responses of lymph-node involved (stage III) melanoma patients to adjuvant dendritic cell vaccination with subsets of naturally occurring dendritic cells (nDCs). Fifteen patients with completely resected stage III melanoma were randomized to receive adjuvant dendritic cell vaccination with CD1c + myeloid dendritic cells (cDC2s), plasmacytoid dendritic cells (pDCs) or the combination. Immunological response was the primary endpoint and secondary endpoints in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…In 64% of the patients, functional IFN-γ-producing T cells were found in the skin test. Only low-grade adverse events were observed [40].…”
Section: Primary Naturally Circulating Dendritic Cells: More Potent V...mentioning
confidence: 98%
“…In 64% of the patients, functional IFN-γ-producing T cells were found in the skin test. Only low-grade adverse events were observed [40].…”
Section: Primary Naturally Circulating Dendritic Cells: More Potent V...mentioning
confidence: 98%
“…A mixed response was described in one out of fifteen evaluable patients, but none obtained an overall tumor response. Other groups have reported that vaccination with natural classic and pDCs is safe and feasible [ 138 ]. Another innovative clinical trial selected Langerhans-type DC (CD83+ CD86 bright HLA-DR bright CD14 neg ) obtained ex vivo from CD34+ cells from the peripheral blood of resected stage IIB to IV melanoma patients.…”
Section: DC Vaccines In Solid Tumorsmentioning
confidence: 99%
“…Although cDCs may be superior to MoDCs in their ability to stimulate T cells (7,103), there are currently no established protocols for isolating or differentiating these cells in vitro. Nonetheless, in some diseases, most notably melanoma, the use of cDCs and pDCs as DC vaccines has shown some encouraging early results that may be extended to GBM research in the future (104)(105)(106)(107).…”
Section: Overview Of DCV Clinical Trials 41 the Source Of Dcsmentioning
confidence: 99%